2021
DOI: 10.1111/evj.13474
|View full text |Cite
|
Sign up to set email alerts
|

Postprandial insulin responses to various feedstuffs differ in insulin dysregulated horses compared with non‐insulin dysregulated controls

Abstract: Background: Controlling postprandial hyperinsulinaemia is important in insulin dysregulated (ID) horses to reduce the risk of laminitis. Objectives: To evaluate postprandial insulin responses of ID versus non-insulin dysregulated (NID) horses to feedstuffs varying in nonstructural carbohydrate (NSC) and crude protein (CP). Study design: Randomised crossover. Methods: Eighteen adult mixed-breed horses (13.3 ± 2.2 years; 621 ± 78.8 kg) were individually fed [~1 g/kg body weight (BW)] specific feedstuffs within t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 38 publications
4
13
0
1
Order By: Relevance
“…Although neither of the above studies were conducted in the ID animal, practical recommendations were developed from them 9,11 . Therefore, dietary recommendations should be developed in the ID horse 12 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although neither of the above studies were conducted in the ID animal, practical recommendations were developed from them 9,11 . Therefore, dietary recommendations should be developed in the ID horse 12 …”
Section: Introductionmentioning
confidence: 99%
“…If individual ID animals require minimal postprandial insulin responses to reduce the risk of HAL, it would be useful to have guidelines for these high‐risk animals. Recent work has shown a possible threshold for starch between 0.024 and 0.054 g/kg bwt and for NSC between 0.076 and 0.191 g/kg bwt in ID horses above which augmented insulin responses may occur 12 . Thus, the current study aimed to elucidate if ID horses do indeed have a threshold (i.e., above which an augmented insulinaemic response occurs which is significantly higher than non‐ID horses' response to the same diet) for NSC, specifically pure WSCs and starch, by evaluating the insulin response (incremental area under the curve for insulin [IAUCi] and peak insulin concentrations) to seven different diets that varied in their WSC and starch content.…”
Section: Introductionmentioning
confidence: 99%
“…Some caution should be taken with ration balancers that have higher protein, as those have been shown to induce a more pronounced insulin response, albeit not as dramatic as that of higher nonstructural carbohydrate feeds. 95,96 Additionally, if grain is fed, stationary objects placed below the feed are most effective at slowing down the time it takes horses to eat food, which may blunt the postprandial insulin and glucose peaks. 97 Caloric restriction should be undertaken in overconditioned or obese horses to induce weight loss.…”
Section: Current Nutritional Recommendations For Equines With Endocri...mentioning
confidence: 99%
“…Recommendations for the management of animals with ID are aimed at the mitigation of postprandial hyperinsulinaemia, including the restriction of access to grass and forage with NSC contents >10–12% on a DM basis (Geor & Harris, 2013). Recent work has suggested that severely insulin dysregulated animals can have exaggerated insulinaemic responses to even small intakes of complementary feeds, with a threshold of between 0.08 and 0.15 g NSC/kg BW (Macon et al., 2022). Practically, based on this work, severely insulin dysregulated animals should be restricted to 0.1 g NSC/kg BW per meal if a very low insulin response is required.…”
Section: Nutritional Considerations For the Management Of Ppidmentioning
confidence: 99%